Integrated Water Management Practical Experiences and Case Studies - Meire, Patrick; Coenen, Marleen; Lombardo, Claudio; Robba, Michela; Sacile, Roberto; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
It is widely stipulated that the world$1 (Bs water supply will come to symbolize the blue gold of the 21st century. As such, it is essential that further efforts be invested in developing practical means for managing this natural wealth, in order to avoid any possible threat of depletion, contamination or adverse side effects for the societies who depend on it. Water is a limited resource, and human beings and their subsequent anth- pogenic processes can cause subtle but drastic variations in its quantity and quality, which can in turn result in changes to the source$1 (Bs related ecosystem. The EC directive 2000/60 introduced a whole range of specific definitions, objectives and constraints regarding the various aspects of water management, including water quality management, policies, economic aspects, ecology, price, and sustainable development. These issues all require the formulation of common, integrated, sustainable approaches for managing the water system from a multidisciplinary perspective, and the definition of new professional skills, requirements which become even more evident where transboundary areas are concerned. In order to take decisions in an equitable, sustainable, and ethical fashion, water resource management does in fact call for extensive knowledge of the complex relationships between citizens and their water system. The book represents a practical contribution made possible thanks to the efforts of scientists from NATO countries and partners, along with Belgium and Italy$1 (Bs collaboration on Integrated Water Management and its possible risk factors, including problems related to targeted terrorist acts.s
Concepts and Approaches of Integrated Water Management -- Filling the Information Gap between Water Systems and Decision Makers in the Sustainable Development of a Territory -- Towards an Adaptive Approach in Planning and Management Process -- The Value of the Italian Civil Protection System in Integrated Water Management For The Mediterranean Environment -- Knowledge Discovery in Environmental Data -- NetSyMoD - An Integrated Approach for Water Resources Management -- Water Conflicts: An Unavoidable Challenge from the Transboundary to the Local Dimension -- Case Studies -- An Eco-Hydrological Project on Turkey Creek Watershed, South Carolina, U.S.A -- Integrated Transboundary Management of Lake Constance Driven by the International Commission for the Protection of Lake Constance (IGKB) -- Integrated Water Mangement in the Seven Cities Basin -- Establishment of the Iskar Reservoir Minimum Sanitary Storage Capacity -- Eutrophication in the Blackwater River Catchment, Ireland -- The Proposal of IWRM in the Bouregreg Basin and How it Fits with the UNESCO/HELP Policy Program -- Impact of the Ignalina Nuclear Power Plant on the Druksiai Cooler - Lake -- Transboundary River Contract Semois-Semoy Between Belgium (Wallonia) and France -- Ground and Water Levels Change in the Scheldt Basin -- The Architecture of a Decision Support System (DSS) for Groundwater Quality Preservation in Terceira Island (Azores) -- Greece: Ecosystem Based IWM Plans in the Framework of WFD Implementation: The (3z(BStrymon(3y (BPilot Project -- The Role of the Help Programme -- Participation Aspects in the Realisation of the Nete River Basin Management Plan: Methodology and Application -- The Use of Hydrological Characteristics for Wetland Habitats Protection in Water Management of the Upper Narew River System -- Saltwater Intrusion in a Unconfined Coastal Aquifer: The Case Study of Cervia (North Adriatic Sea, Italy) -- International and Inner Transboundary River Basins in the Kaliningrad Oblast, South-Eastern Baltic -- Reports of the Working Groups -- Environmental Indicators for Water Resources Management -- Developments in Participation within Integrated Water Management -- Conclusion.s
Keywords: Environment; Environmental management; Ecosystems; Water pollution; Environment; Environmental Management; Water Policy/Water Governance/Water Management; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Ecosystems; Environmental Monitoring/Analysis.; Electronic books